Peran Manager Puncak Sebagai Pemoderasi Tekanan Eksternal, Komitmen Organisasi dan Pengendalian Internal Pada Kinerja Anggaran - Aminah, Siti; ., Soeratno; ., Suyanto (Institut Bisnis dan Informatika Kesatuan, 2017)
This study aims to analyze the extend of the role of top manager can influence the relationshio of external pressure and internal control on the public organization’s budget performance. The samples are used in this study were 91 questionnaires are filled based on employees and strucural officials perceptions who are directly involved in the budgeting process at KPK. This study aims to analyze the extend of the role of top manager can influence the relationshio of external pressure and internal control on the public organization’s budget performance. The samples are used in this study were 91 questionnaires are filled based on employees and strucural officials perceptions who are directly involved in the budgeting process at KPK. The method of analysis used in processing the data using the method of Ordinary Least Square (OLS) model of multiple regression equation with residual test. Dependent variable in this study is budget performance. Independent variables are external pressure, organizational commitment and internal control. The role of top manager is used as a moderating variable. The results show that the role of top managers can influence the relationship of external pressure and internal control on budget performance. External pressure, organizational commitment and internal control variables have an individual effect on budget performance with a significance <0.005.